Technical and Economic Efficiency of Rice Production in the Kou Valley (Burkina Faso): Stochastic Frontier Approach - Ouedraogo, Souleymane (Asian Journal of Agriculture and Rural Development, 2015)
The present paper seeks to deal with the issue of technical and economic efficiency of rice producers in the Kou valley, located in the region of the high basins in the western part of Burkina Faso. The stochastic frontier approach was used to estimate the production function, from a Cobb-Douglas stochastic frontier function and its dual which allow the estimation of the technical, allocative and economic efficiencies. The determinants of efficiency were simultaneously assessed along with the frontier functions through the FRONTIER 4.1 software. The data used herein are from a survey encompassing 130 rice producers, randomly chosen. Results show that farm size, fertilizer used, years of experience and literacy are the explicative factors of rice production in the Kou valley. The costs of the different production factors significantly contribute to explain the total production cost, and that is in concordance with the economic theory. The technical, allocative and economic efficiencies of producers are, on average, 80.15%, 92.7% and 74.43% respectively. A 25% improvement of rice production is possible if producers optimize their economic efficiency.